Post-fire restoration of soil microbial communities in a Quercus suber population - Costa, Eunice Conceição Lima da (2020)
Wildfires cause disturbances with huge impact on Portuguese cork oak forests. Due to the production of cork, Quercus suber L. trees are recognized to be well-adapted to fires occurrence and to high temperatures. However, cork oak sustainability is also largely dependent on soil microbial communities, such as the presence of ectomycorrhizal fungi or rhizobacteria. In this work, the effects of temperature on cork oak soil microbial communities was studied, as well as the ecological restoration of Quercus suber forests after a wildfire episode. An evaluation of soil microbial specific death rate was performed using temperature assays (50ºC to 125ºC) on soils collected from cork oak trees. The most temperature resistant bacteria were identified by sequencing. Results revealed an increase of microbial death specific rate with temperature. Bacterial communities were more heat sensitive than fungi, as their survival is probably ensured by spore production. Accordingly, spore-forming bacteria such as Bacillus spp were identified as the most heat resistant bacteria. In addiction bacterial community analysis by a metabarcoding approach revealed high abundance of Firmicutes (Bacillus) on soil samples subjected at 100ºC for 15 and 30 min. Furthermore, these results provided a prediction of what could happen to bacterial communities after a wildfire in cork oak forests. Taking advantage from the natural occurrence of a natural wildfire in Santa Marta das Cortiças (Braga), cork oak soil microbial communities were surveyed using a metabarcoding approach. Soil samples from nine trees with three different types of fire damage (burnt, half-burnt and non-burnt) were collected, and bacterial community compared along time. Results revealed that from 5- to 18-months post-fire, there are differences on the composition of bacterial communities. A higher incidence of gram-negative bacteria (Proteobacteria), followed by Acidobacteria, Actinobacteria and Chloroflexi were always found for all cork oak soils. The variation on microbial communities among fire-affected soils is explained by differences on soil chemical composition, fire intensity and edaphoclimatic factors.